An improved procedure for isolation of high-quality RNA from nematode-infected Arabidopsis roots through laser capture microdissection. Issue 1 (December 2016) - Anjam, Muhammad; Ludwig, Yvonne; Hochholdinger, Frank; Miyaura, Chisato; Inada, Masaki; Siddique, Shahid; Grundler, Florian
Abstract Background Cyst nematodes are biotrophs that form specialized feeding structures in the roots of host plants, which consist of a syncytial fusion of hypertrophied cells. The formation of syncytium is accompanied by profound transcriptional changes and active metabolism in infected tissues. The challenge in gene expression studies for syncytium has always been the isolation of pure syncytial material and subsequent extraction of intact RNA. Root fragments containing syncytium had been used for microarray analyses. However, the inclusion of neighbouring cells dilutes the syncytium-specific mRNA population. Micro-sectioning coupled with laser capture microdissection (LCM) offers an opportunity for the isolation of feeding sites from heterogeneous cell populations. But recovery of intact RNA from syncytium dissected by LCM is complicated due to extended steps of fixation, tissue preparation, embedding and sectioning. Results In the present study, we have optimized the procedure of sample preparation for LCM to isolate high quality of RNA from cyst nematode induced syncytia in Arabidopsis roots which can be used for transcriptomic studies. We investigated the effect of various sucrose concentrations as cryoprotectant on RNA quality and morphology of syncytial sections. We also compared various types of microscopic slides for strong adherence of sections while removing embedding material. Conclusion The use of optimal sucrose concentrations as cryoprotection plays a key role in RNA stability and morphology of sections. Treatment with higher sucrose concentrations minimizes the risk of RNA degradation, whereas longer incubation times help maintaining the morphology of tissue sections. Our method allows isolating high-quality RNA from nematode feeding sites that is suitable for downstream applications such as microarray experiments.